OUTSOURCING DALAM UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (DITINJAU DARI ASPEK 222 KEADILAN, KEPASTIAN, DAN KEMANFAATAN HUKUM) - Maulana Saputra Sauala (UNISSULA, 2015)
Outsourcing system ilegalized by law No. 13 of 2003 on employment especially in chapters 64-66, so it can be examined that the legislators themselves are agents of the canal for entrepreneursand the state on the other hand through his government also supports this activity. That is, hereit is clear that the political forces affecting the massive law. Here there is clearly a dichotomybetween countries as legislators / wisdom with the community as the goal of the legislation. The implication is due to the dichotomy of law acts as a tool to manipulate the state of socialrelations, even openly law the interests of the groups that control the state in this case is thecapital owners / entrepreneurs.It can be concluded the law is for humans and confirmed the existence of human beings asa whole person, so that the passage of the law is also the needs of the community itself. But if the opposite happens, ie, as described above, it can be ascertained that the law certainly got loud opposition from people who put themselves as victims, in this case the state would not be able to protect the interests of the people especially the workers’ interests